2010
DOI: 10.1093/nar/gkq1049
|View full text |Cite
|
Sign up to set email alerts
|

Late steps of ribosome assembly in E. coli are sensitive to a severe heat stress but are assisted by the HSP70 chaperone machine

Abstract: The late stages of 30S and 50S ribosomal subunits biogenesis have been studied in a wild-type (wt) strain of Escherichia coli (MC4100) subjected to a severe heat stress (45–46°C). The 32S and 45S ribosomal particles (precursors to 50S subunits) and 21S ribosomal particles (precursors to 30S subunits) accumulate under these conditions. They are authentic precursors, not degraded or dead-end particles. The 21S particles are shown, by way of a modified 3′5′ RACE procedure, to contain 16S rRNA unprocessed, or proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 82 publications
5
31
0
Order By: Relevance
“…Second, intermediates from the Δ rimM strain show underrepresented levels for all secondary and tertiary binding proteins from the 3′-domain. Interestingly, the Δ rimM intermediates are to some extent similar in protein composition to a previously identified in vivo 21S intermediates (44,53), but differ from the in vitro RI intermediates (54). The close resemblance of the Δ rimM intermediates to the naturally populated in vivo 21S intermediates suggests that they represent an early stage during the assembly of the 3′-domain, likely the entry stage.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Second, intermediates from the Δ rimM strain show underrepresented levels for all secondary and tertiary binding proteins from the 3′-domain. Interestingly, the Δ rimM intermediates are to some extent similar in protein composition to a previously identified in vivo 21S intermediates (44,53), but differ from the in vitro RI intermediates (54). The close resemblance of the Δ rimM intermediates to the naturally populated in vivo 21S intermediates suggests that they represent an early stage during the assembly of the 3′-domain, likely the entry stage.…”
Section: Discussionsupporting
confidence: 54%
“…Identification of the two sets of 16S rRNA precursors by a previously established 5′3′-rapid amplification of complementary DNA ends (RACE) technique (44) reveals that a majority of these precursors are unprocessed at both the 5′- and 3′-ends (Supplementary Figure S1). The protein gel analysis shows that some ribosomal proteins, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DnaK–DnaJ chaperone system has been shown to contribute to ribosome biogenesis, although a specific mechanism has not been determined (Al Refaii and Alix, ; René and Alix, ). To test if the transposon insertions into dnaK had also suppressed the GraT‐caused ribosome defects, we examined the ribosome profiles.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that rhodomyrtone inhibited the synthesis of DnaK protein in the treated pathogens (Sianglum et al, 2011). DnaK protein is associated with a wide variety of cellular processes (Hu et al, 2006;Kurt et al, 2006;Singh et al, 2007;Al Refaii & Alix, 2009;René & Alix, 2011), and deletion of dnaK in S. aureus demonstrated an increase in susceptibility to oxidative stress conditions and reduced carotenoid production (Singh et al, 2007). Sigma factor s B was significantly downregulated in rhodomyrtone-treated S. aureus cells (Sianglum et al, 2012).…”
Section: Discussionmentioning
confidence: 99%